Landscape of Faith: Black Churches in Wabaunsee County, Kansas, 1881-1981 and The Black Baptist Church in Eskridge, Kansas, 1887-1963 - Bush, Rebecca (Kansas State University. Dept. of History. Chapman Center for Rural Studies, 2010)
Rebecca Bush uses information gleaned from a year-long research project on locations and roles of early African American churches in Wabaunsee County. Although no church building yet stands, she has confirmed the sites of at least eight Baptist and AME churches through fieldwork, interviews, and early maps. She provides a case study of the Eskridge black Baptist Church prior to 1950. Included is a map with church sites identified and marked.
Keywords: African American; Wabaunsee County; Churches; Eskridge